2023
DOI: 10.1371/journal.pgph.0000402
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of three computer-aided detection systems for detecting pulmonary tuberculosis on chest radiography when used for screening: Analysis of an international, multicenter migrants screening study

Abstract: The aim of this study was to independently evaluate the diagnostic accuracy of three artificial intelligence (AI)-based computer aided detection (CAD) systems for detecting pulmonary tuberculosis (TB) on global migrants screening chest x-ray (CXR) cases when compared against both microbiological and radiological reference standards (MRS and RadRS, respectively). Retrospective clinical data and CXR images were collected from the International Organization for Migration (IOM) pre-migration health assessment TB s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…One study compared Genki to other CAD algorithms and noted similar specificity to CAD4TB and qXR, while we found it to be overall less specific. 11 However, that study assessed CAD in a screening cohort and was conducted in Vietnam where we also found Genki had higher specificity, highlighting the importance to conduct a multi-country evaluation to assess performance. To our knowledge this is the first published work to assess and compare DrAid, and although lower accuracy than the above three algorithms, overall it performed well with 68% specificity at 90% sensitivity.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…One study compared Genki to other CAD algorithms and noted similar specificity to CAD4TB and qXR, while we found it to be overall less specific. 11 However, that study assessed CAD in a screening cohort and was conducted in Vietnam where we also found Genki had higher specificity, highlighting the importance to conduct a multi-country evaluation to assess performance. To our knowledge this is the first published work to assess and compare DrAid, and although lower accuracy than the above three algorithms, overall it performed well with 68% specificity at 90% sensitivity.…”
Section: Discussionmentioning
confidence: 78%
“…Multiple analyses have found that the CAD threshold to classify TB may need to be adjusted for different settings and populations, but head-to-head comparisons of CAD products with these thresholds have been limited to one or two countries, 8,9 retrospective meta-analyses, 10 or for the screening use-case. 11,12 An independent, head-to-head comparison of the diagnostic accuracy of CAD algorithms in a large, diverse, multi-country cohort of individuals with presumptive pulmonary TB is needed to address these issues. We thus conducted a prospective diagnostic accuracy study across seven countries in sub-Saharan Africa, South Asia, and Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis mirrors a similar approach that has been described in other studies evaluating CXR-CAD for TB. (16, 21) Subgroup analysis was performed based on country, site, age group, sex, symptoms, diabetes status (if known), and HIV status (if known). Results were presented for CXR-CAD sensitivity and specificity with 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to sharing of DICOM images with FIND, identifying information was removed by use of a previously described DICOM anonymizing tool. (16) Patient clinical data and radiologist interpretations were aggregated and duplicate study subjects were excluded prior to analysis.…”
Section: Data Collectionmentioning
confidence: 99%
“…CXR implementation for TB screening has been limited in resource-constrained settings due to centralized CXR infrastructure [ 3 ] and scarcity of skilled personnel for interpretation [ 4 ]. The advent of digital CXR with computer-aided detection (CAD) analysis may reduce barriers to CXR screening by quickly enabling screening without the need for a skilled reader [ 5 , 6 ]. However, performance varies by population screened, and limited data are available for children [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%